Cylindrical antennas and arrays - King, Ronold Wyeth Percival (Cambridge University Press, 2002)
This book explains in great detail how to design, analyse and test such arrays from a practical engineering standpoint. Written by three of the leading engineers in the field, and based on world-class research carried out at Harvard over the last 40 years, Cylindrical Antennas and Arrays is destined to be come established as the basic reference for engineers and advanced students for many years to come.